Hypercalcemia associated with isolated bone marrow sarcoidosis in a patient with underlying monoclonal gammopathy of undetermined significance: case report and review of literature. Issue 1 (December 2016) - Gubatan, John; Wang, Xiaohui; Louissaint, Abner; Mahindra, Anuj; Vanderpool, John
Abstract Background Bone marrow sarcoidosis is extremely rare. The association between sarcoidosis and lymphoproliferative disorders has been previously speculated, although the diagnosis of sarcoidosis often precedes any hematological derangements. Case presentation Here, we report for the first time, a case of a 57-year-old Caucasian woman with a previous diagnosis of monoclonal gammopathy of undetermined significance (MGUS) developing hypercalcemia and renal failure with workup notable for isolated bone marrow sarcoidosis and not multiple myeloma as expected. The patient was successfully managed with prednisone taper therapy with resolution of her hypercalcemia and repeat bone marrow biopsies demonstrating resolving granulomas. Conclusions Our case illustrates the diagnostic challenges associated with bone marrow sarcoidosis and suggest that chronic immune stimulation in the bone marrow in the setting of MGUS may be associated with the development of localized sarcoidosis. The long term consequences of steroid therapy targeting sarcoidosis in this patient with underlying MGUS remain unknown. Greater surveillance and closer followup is planned in light of the increased risk of malignant transformation of MGUS into multiple myeloma in the setting of bone marrow sarcoidosis.